How to optimize communication about animal and animal-free research methods - Homberg, Judith Regina; Piersma, Aldert H.; Krul, Cyrille A. M.; Genzel, Lisa; Kienhuis, Anne; ter Gast, Ellen; Wolvekamp, Monique (Frontiers in Veterinary Science, 2024)
There is a long-standing debate about experimental non-human animals and animal-free methods in scientific research. Among the various stakeholders involved in the debate are the scientists. During media broadcasts we, animal researchers and animal-free methods researchers, were positioned as 'opponents'. In this essay we describe our initial rational thoughts and emotions after these events, and how we came together to explore our common ground on animal(-free) experimentation. Realizing that all models have advantages and limitations, our common ground lies in the principles of good scientific research and responsible experimentation. Our communication emanating from the broadcasts has been instrumental in improving communication on animal(-free) experimentation issues by teaming up. We strongly believe that this is essential for making well-informed decisions for the methods we are using now and will be using in the future.